Proceedings of the 2019 CHI Conference on Human Factors in Computing Systems 2019
DOI: 10.1145/3290605.3300332
|View full text |Cite
|
Sign up to set email alerts
|

Finding Information on Non-Rectangular Interfaces

Abstract: With upcoming breakthroughs in free-form display technologies, new user interface design challenges have emerged. Here, we investigate a question, which has been widely explored on traditional GUIs but unexplored on non-rectangular interfaces: what are the user strategies in terms of visual search when information is not presented in a traditional rectangular layout? To achieve this, we present two complementary studies investigating eye movements in different visual search tasks. Our results unveil which area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Concerning the shapes, overall participants preferred the rectangular rounded shape for icons and images, and the rectangular shape for text. These results complement previous work on the perception of non-rectangular interfaces [44][45][46], which mostly focused on static content .…”
Section: Discussionsupporting
confidence: 88%
“…Concerning the shapes, overall participants preferred the rectangular rounded shape for icons and images, and the rectangular shape for text. These results complement previous work on the perception of non-rectangular interfaces [44][45][46], which mostly focused on static content .…”
Section: Discussionsupporting
confidence: 88%
“…By extension, in this paper we consider a freeform device any device not having a rectangular shape, in contrast to current laptops or smartphones for instance. Research on Freeform devices has mostly focused on the design of non-rectangular content according to static shape features [31,32,34], or on how to dynamically organize its content according to the available display surface [25].…”
Section: Freeform Interfacesmentioning
confidence: 99%
“…In this paper, we address this gap by specifically examining freeform devices, or 'Stranger Screens', in the context of applications they benefit. This work takes a complementary approach to recent developments in freeform device research [31,32,34], that has involved limited perspectives beyond those of the research community. In contrast to past literature on SCIs, our work moves away from looking at the transformation of the devices and rather investigates the state of the device at a given time.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al ( 2021 ) found that compared to other areas of the smartphone screen, users gave a significantly longer total attention time is significantly longer and the first fixation time is also mainly in the bottom area of the interface, so we can optimize the layout of the mobile application interface according to the allocation of user attention. In a visual environment with an increasing amount of available information and high information density, visual search interfaces can be optimized through techniques such as layout design, styling, and dynamic presentation to improve the efficiency of users' visual search (Gaona-Garcia et al, 2017 ; Simon et al, 2019 ; Pan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%